FAKTOR SOSIOLOGIS KESULITAN BELAJAR SISWA PADA MATA PELAJARAN SOSIOLOGI DI KELAS X SMA PGRI 1 PADANG - Ningsih, Desi Kurnia; Erianjoni, Erianjoni; Erningsih, Erningsih (Pendidikan Sosiologi, 2014)
Â Factors that affect learning can provide positive support in learning, but can also inhibit the learning process. Barriers that occur impact on learning outcomes of individuals who experience the learning process is not as expected. Difficulties are often experienced would be a very significant barrier to further the learning process, as it can lead to low student achievement. Objectives to be achieved in this study are : to determine the sociological factors on student learning difficulties sociology subjects in class X SMA PGRI 1 Padang. The theory used in this study is the theory of behaviorisme. In behavioristik flow, learning is essentially the formation of associations between sensory impression captured by a tendency to act or the relationship between stimulus and response. This study used a qualitative research approach. This type of research used in this study is descriptive to express concerns about the sociological factors on student learning difficulties sociology subjects. In this study, the determination of informants conducted by purposive sampling technique, in this study, are the students and teachers of class X subjects of sociology, Principal, High School Principal at Vice PGRI 1 Padang. The data of this study is primary data obtained through interviews. The unit of analysis is the group with the analysis of the data comprising the steps of reduction, data presentation / analysis of data, and drawing conclusions. The results of this study are : ( 1 ) Internal factors cause difficulty in studying sociology student from one of the students is, students do not utilize well as learning resources, Â read the handbooks are recommended teachers, students therefore difficult to understand the subject matter of sociology. It also comes from a lack of student motivation, due to laziness students in doing the task and answer the questions provided by the teacher about the lesson that has been taught, so that the desired learning outcomes are not achieved properly. ( 2 ) external factors difficulties experienced by students in learning sociology teacher education factor interaction with students is, due to the way the lead teacher in the learning process does not use a variation, which causes saturation partially students to follow the learning process, so that students tend to get bored with the lessons taught teacher.